THE INFLUENCE OF PRICE AND SERVICE QUALITY OF THE SHOPEEFOOD APPLICATION ON CONSUMER PURCHASING DECISIONS - Farida, Nur; Kurniawan, Ilham (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. The price set by the company must follow the benefits provided so that consumers will make purchasing decisions. Service quality determines the success or failure of consumers in making purchasing decisions. Research Purpose. This research discusses the influence of price and application service quality ShopeeFood on consumer purchasing decisions in Pekauman Village, Gresik District. Research Method. The object of this research is Pekauman Village, Gresik District. A total of 69 data were collected using the questionnaire method. Findings. The results of the research show that price has a positive and insignificant influence on consumer purchasing decisions in the Pekauman sub-district, Gresik sub-district. The service quality has a positive and significant effect on consumer purchasing decisions in the Pekauman sub-district, Gresik sub-district. Conclusion. Finally, price and service quality simultaneously influence consumer purchasing decisions in the Pekauman sub-district, Gresik sub-district.